Dork diaries - Russell, Rachel Renee (Simon & Schuster, 2015)
This set includes the following: Dork Diaries, Party Time, Pop Star, Skating Sensation, Dear Dork, Holiday Heartbreak, TV Star, Once Upon a Dork, Drama Queen, Puppy Love, Frenemies Forever and Crush Catastrophe!